Acute Illness Is Associated with Suppression of the Growth Hormone Axis in Zimbabwean Infants - Jones, Andrew D. (Am J Trop Med Hyg, 2015)
Frequent infections contribute to childhood stunting in developing countries but the causal pathways are uncertain. We tested the hypothesis that intercurrent illnesses suppress the growth hormone axis through reductions in insulin-like growth factor 1 (IGF-1). In a birth cohort of 202 HIV-unexposed Zimbabwean infants, we analyzed data on 7-day illness recall and measured plasma interleukin-6, C-reactive protein, alpha-1-acid glycoprotein, and IGF-1 by enzyme-linked immunosorbent assay, at age 6 weeks, and then 3, 6, 12, and 18 months. Children with recent acute illness had lower IGF-1 concentrations than healthy children and IGF-1 correlated inversely (P < 0.05) with inflammatory biomarkers at most time points between 3 and 18 months. Using path analysis, we showed that cough and fever had a predominantly indirect effect on suppressing IGF-1, through the acute-phase response, whereas diarrhea had a predominantly direct effect on IGF-1. Acute illness may therefore impact the growth hormone axis through both direct and indirect pathways.